PENELITIAN TEKNOLOGI PEMBELAJARAN BERDASARKAN PENDEKATAN SISTEM - Salamah, Salamah (MAJALAH ILMIAH PEMBELAJARAN, 2008)
Human development in contextual way has concerned with cultures, values and norms; hence, from time culture covers education. Individual integrated educational process, in essence, turns out to be a cultural transfer process. Science and technology exist and develop based on given culture and crystalized as entities, sciences and technologies. This article relates to scientific and technological contributor.